Analisis Kesalahan Konsep Matematika Pada Mahasiswa Program Studi Pendidikan Fisika (Studi Kasus Pada Materi Kinematika Dengan Analisis Vektor) - Muhammad Fachrurrozy; Muslimin Muslimin; Sahrul Saehana (Mitra Sains, 2017)
Mathematics errors give great effects in physics problem solving, thus the using of mathematics in physics is indispensable because both of them are structured knowledge. The objective of this research is to describe mathematics concepts errors of undergraduate students of Physics education study program on kinematics concepts using vector analysis. Data were gained from students’ answer sheets and Thinking-Aloud recording. The errors of mathematic concepts and procedures were analysed using Kastolan, then elaborated how students use mathematics in physics problem solving. This research was conducted at Teacher Training and Education Faculty of Tadulako University and research’ subjects were 5 undergraduate students of Physics education study program which were chosen by purposive sampling methods based on their basic physics subject mark. The results show that mathematics has crucial role for students in physics problem solving. Percentage of students’ mathematics errors in integral concepts is 50%, differential concepts is 20%, distributive of mathematics is 20%, whereas mathematics procedures errors embody 50% of integral operation errors, 20% of differential errors, 80% of exponent differential errors and trigonometry, 60% of fraction operation and 20% of calculation operation. These results indicate the lack of respondents’ mathematics concepts understanding specially in exponent differential and trigonometry concepts and enact the unit vectors.